(untitled) (Journal of Plant Disease Sciences, 2019)
In the recent years, symptoms of berry rot were observed on field plants of Coffea arabica L. during rainy seasons in the farm of Central Coffee Research Institute, Balehonnuru, India. The disease was characterized by the appearance of small, black coloured, slightly sunken necrotic lesions usually near the stalk region of developing green berries which progress towards the distal end of berries. At later stage sporodochia of the pathogen with shiny black center and white margin appears in concentric rings. The rotting of stalk region leads to dropping of developing berries. The causative agent was identified as Myrothecium roridum based on the morphological data and pathogenicity test.